Public opinion and the news media - Frank Senge Kolma (Asia Pacific Network, 1997)
During the elections the news media, both as a corporate citizen and as the conveyor of events, happenings and decisions to the masses, is called upon to exercise more care and responsibility than at any other time. An innocent looking news article could spell doom for a political party or a leader.